BMP-2 Grafted nHA/PLGA Hybrid Nanofiber Scaffold Stimulates Osteoblastic Cells Growth. (11th October 2015) - Haider, Adnan; Kim, Sukyoung; Huh, Man-Woo; Kang, Inn-Kyu
Abstract : Biomaterials play a pivotal role in regenerative medicine, which aims to regenerate and replace lost/degenerated tissues or organs. Natural bone is a hierarchical structure, comprised of various cells having specific functions that are regulated by sophisticated mechanisms. However, the regulation of the normal functions in damaged or injured cells is disrupted. In order to address this problem, we attempted to artificially generate a scaffold for mimicking the characteristics of the extracellular matrix at the nanoscale level to trigger osteoblastic cell growth. For this purpose, we have chemically grafted bone morphogenetic protein (BMP-2) onto the surface of L-glutamic acid modified hydroxyapatite incorporated into the PLGA nanofiber matrix. After extensive characterization using various spectroscopic techniques, the BMP-g-nHA/PLGA hybrid nanofiber scaffolds were subjected to various in vitro cytocompatibility tests. The results indicated that BMP-2 on BMP-g-nHA/PLGA hybrid nanofiber scaffolds greatly stimulated osteoblastic cells growth, contrary to the nHA/PLGA and pristine PLGA nanofiber scaffold, which are used as control. These results suggest that BMP-g-nHA/PLGA hybrid nanofiber scaffold can be used as a nanodrug carrier for the controlled and targeted delivery of BMP-2, which will open new possibilities for enhancing bone tissue regeneration and will help in the treatment of various bone-related diseases in the future.